The telephone gambit : chasing Alexander Graham Bell's secret - Shulman, Seth (New York : W. W. Norton & Co., 2008)
Although Alexander Graham Bell is widely accepted as the father of the telephone (despite the fact that rival inventor Elisha Gray submitted a similar claim the same day Bell filed his patent), Schulman provides intriguing evidence questioning if the scales were deliberately tipped in Alexander's favor
Bibliografische referenties ; index
Keywords: Bell, Alexander Graham, -- 1847-1922.; Gray, Elisha, -- 1835-1901.; Inventors -- United States -- Biography; Telephone -- Patents